Ophthalmic complications of endoscopic sinus surgery - Seredyka-Burduk,Malgorzata (2017)
Abstract Introduction: The proximity of the paranasal sinuses to the orbit and its contents allows the occurence of injuries in both primary or revision surgery. The majority of orbital complications are minor. The major complications are seen in 0.01-2.25% and some of them can be serious, leading to permanent dysfunction. Objective: The aim of this study was to determine the risk and type of ophthalmic complications among patients operated due to a chronic rhinosinusitis. Methods: This is a retrospective study of 1658 patients who underwent endoscopic sinus surgery for chronic rhinosinusitis with or without polyps or mucocele. Surgeries were performed under general anesthesia in all cases and consisted of polyps' removal, followed by middle metal antrostomy, partial or complete ethmoidectomy, frontal recess surgery and sphenoid surgery if necessary. The ophthalmic complications were classified according to type, frequency and clinical findings. Results: In our material 32.68% of the patients required revision surgery and only 10.1% had been previously operated in our Department. Overall complications occurred in 11 patients (0.66%). Minor complications were observed in 5 patients (0.3%) with the most frequent being periorbital ecchymosis with or without emphysema. Major complications were observed in one patient (0.06%) and were related to a lacrimal duct injury. Severe complications occurred in 5 cases (0.3%), with 2 cases and referred to a retroorbital hematoma, optic nerve injury (2 cases) and one case of extraocular muscle injury. Conclusions: Orbital complications of endoscopic nasal surgery are rare. The incidence of serious complications, causing permanent disabilities is less than 0.3%. The most important parameters responsible for complications are extension of the disease, previous endoscopic surgery and coexisting anticoagulant treatment.